Removal of Cr, Ni and Co in the water of chromium mining areas by using Lemna gibba L. and Lemna minor L - Sasmaz, Ahmet; Dogan, Ibrahim Mete; Sasmaz, Merve (Wiley, 2016)
This study investigated the use of Lemna gibba and Lemna minor plant species to absorb Cr, Ni and Co from Alacakaya mining area water. Lemna gibba and L. minor were separately placed to feed into two reactors. Water and plant samples were collected for eight consecutive days, and the pH, electric conductivity and temperature of the water were measured. The plants were washed, dried and burned at 300 degrees C for 24 h in a drying oven. The samples were then analysed by ICP-MS (inductively coupled plasma mass spectroscopy) for concentrations of Cr, Ni and Co, which were 1.2, 0.9 and 0.5 gL(-1) respectively. On Day 8, the determined uptake of L. gibba and L. minor were: 196 and 398% for Cr; 307 and 1473% for Ni; and 166 and 223% for Co respectively. Lemna gibba and L. minor were thus effective in absorbing Cr, Ni and Co from mining water.
Keywords: accumulation; heavy metals; Lemna gibba L; Lemna minor L; mining water; watertreatment